Looking and listening for learning in arts‐ and humanities‐based creations. Issue 2 (23rd November 2016) - Varpio, Lara; Grassau, Pamela; Hall, Pippa
Abstract : Context: The arts and humanities are gradually gaining a foothold in health professions education as a means of supporting the development of future clinicians who are compassionate, critical and reflexive thinkers, while also strengthening clinical skills and practices that emphasise patient‐centredness, collaboration and interprofessional practices. Assignments that tap into trainee creativity are increasingly used both to prepare learners for the demands of clinical work and to understand the personal and professional challenges learners face in these contexts. Health professions educators need methods for interpreting these creations in order to understand each learner's expressions. This paper describes two theoretical frameworks that can be used to understand trainees' unique learning experiences as they are expressed in arts‐ and humanities‐based creations. Methods: The authors introduce the philosophical underpinnings and interpretation procedures of two theoretical frameworks that enable educators to 'hear' and 'see' the multilayered expressions embedded within arts‐ and humanities‐based student creations: Gilligan's Listening Guide and Kress and van Leeuwen's approach to visual rhetoric. To illustrate how these frameworks can be used, the authors apply them to two creative summaries that learners made as part of a humanities‐informed, interprofessional education intervention that took place in a non‐acute‐care teaching hospital. The interpretations of two creative summaries, a poem and a pair of paintings, highlight how applying these theoretical frameworks can offer important insights into learners' experiences. Conclusions: This cross‐cutting edge paper describes how the Listening Guide and visual rhetoric can help health professions educators listen to and read the arts‐ and humanities‐based creative expressions made by learners. Insights gained from these interpretations can advance the understanding of students' personal experiences in different learning environments and can inform curriculum development.